Fostering Critical Thinking and Environmental Awareness Through Integrated 3R-Based Media Pancasila Student Profile - Ngazizah, Nur; Anjarini, Titi; Suyoto, Suyoto (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to develop and test the feasibility of an Eco-Edutainment learning media that integrates educational games, 3R (Reduce, Reuse, Recycle) materials, and the Pancasila Student Profile framework to enhance students’ critical thinking, creativity, and cooperation in the Natural and Social Sciences (IPAS) subject. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at Purworejo Private Elementary School (SDN Purworejo), Central Java, Indonesia. The population comprised all fourth-grade students, and the sample consisted of 13 students selected through purposive sampling. Data were collected through interviews, observations, expert validation sheets, questionnaires, and pretest–posttest assessments, while data analysis included quantitative descriptive analysis for validity and practicality, and the Normalized Gain (N-Gain) formula to measure effectiveness. The resulting product, titled “Exploring Energy Sources,” consists of three interactive board games designed from recycled materials to facilitate active and enjoyable learning about energy transformation. The research findings show that the media met the feasibility criteria of being very valid, very practical, and effective. These results demonstrate that the Eco-Edutainment model successfully created a meaningful, engaging, and sustainable learning experience while promoting environmental awareness and character competencies aligned with the Pancasila Student Profile.